2007
DOI: 10.1007/s00726-006-0484-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of extrusion on loss and racemization of amino acids

Abstract: The influence of the operation conditions (temperature and residence time) of a thermic treatment on the total amount (free and protein-bound) of amino acid enantiomers of dry fullfat soya was investigated. Total amino acid content was determined using conventional ion-exchange amino acid analysis of total hydrolysates and chiral amino acid analysis was performed by HPLC after precolumn derivatization with o-phthaldialdehyde and 1-thio-beta-D-glucose tetraacetate. Contrary to corn that was investigated previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…A similar decrease in Lys concentration of SBM with increasing the heating temperature above 160°C was also observed in the pilot study reported in Figure 2. These effects have been attributed to formation of Maillard products and cross links among AA (Björck and Asp, 1983;Csapó et al, 2008).…”
mentioning
confidence: 97%
“…A similar decrease in Lys concentration of SBM with increasing the heating temperature above 160°C was also observed in the pilot study reported in Figure 2. These effects have been attributed to formation of Maillard products and cross links among AA (Björck and Asp, 1983;Csapó et al, 2008).…”
mentioning
confidence: 97%
“…Racemization rates of the same amino acid in polyamino acids were much lower than in soy proteins. Related studies [93] showed that: free amino acids racemized approximately ten times slower than did proteinbound ones; alkali treatment of zein induced racemization of amino acids residues and caused nutritional damage without the presence of lysinoalanine (LAL) [94]; serine residues in lactalbumin, leaf protein concentrate, and soy protein were highly susceptible to heat-and alkali-induced racemization [95]; racemization of protein-bound amino acids, especially of lysine, induced by heat extrusion was greater in soy than in corn proteins [96]; melanoidins formed during heating of glucose or fructose with LAA or DAA had similarly shaped but different absorption spectra [97].…”
mentioning
confidence: 98%
“…Chemical hydrolysis (acid or alkaline) will result in a (partial) racemization of the amino acids, where L-amino acids are converted to D-amino acids and vice versa [22]. The degree of racemization depends on hydrolysis conditions, including temperature, pressure, time and chemical composition of the hydrolysis solution, as well as the individual amino acids [2,3,22]. Therefore, analysis of the L-and D-amino acid composition of hydrolyzed samples may be biased.…”
Section: Discussionmentioning
confidence: 99%
“…Industrial processing or fermentation can lead to an increase in D-amino acid levels in food and feed proteins [1][2][3][4]. Consequently, the digestibility and bioavailability of these proteins decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation